2017
DOI: 10.1016/j.ceramint.2017.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Wettability between Fe-Al alloy and sintered MgO

Abstract: In the current study, the wettability between Fe-Al alloy and sintered MgO substrate was investigated. The stable contact angle between the sintered MgO substrate and the liquid iron was approximately 134 o at 1550 o C, hardly influenced by Al concentrations of 18 ppm and 370 ppm in the liquid iron. By changing hydrogen partial pressure from 0 vol% to 1 vol%, the oxygen partial pressure decreased. Meanwhile, the contact angle between the MgO substrate and the liquid iron with 370 ppm Al increased with the decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The wettability between inclusions and molten iron or steel has been widely investigated. [8][9][10][11][12][13][14][15][16][17][18][19][20] However, the values of interfacial energy and contact angle reported in these studies cannot be compared because the studies were conducted under different experimental conditions (e.g., temperature, atmosphere, and crystal orientation). For example, molten Fe and Al 2 O 3 were investigated by Ogino et al, who reported a contact angle of 128° in H 2 atmosphere at 1 873 K. 11) However, Nakashima et al studied the same materials and reported a contact angle of 120° in Ar atmosphere at the same temperature.…”
Section: Evaluation Of Interfacial Energy Between Molten Fe and Fe-18%cr-9%ni Alloy And Non-metallic Inclusion-type Oxidesmentioning
confidence: 99%
“…The wettability between inclusions and molten iron or steel has been widely investigated. [8][9][10][11][12][13][14][15][16][17][18][19][20] However, the values of interfacial energy and contact angle reported in these studies cannot be compared because the studies were conducted under different experimental conditions (e.g., temperature, atmosphere, and crystal orientation). For example, molten Fe and Al 2 O 3 were investigated by Ogino et al, who reported a contact angle of 128° in H 2 atmosphere at 1 873 K. 11) However, Nakashima et al studied the same materials and reported a contact angle of 120° in Ar atmosphere at the same temperature.…”
Section: Evaluation Of Interfacial Energy Between Molten Fe and Fe-18%cr-9%ni Alloy And Non-metallic Inclusion-type Oxidesmentioning
confidence: 99%
“…where γ SV is the gas-solid surface tension, γ LV is the liquidgas surface tension, γ SL the liquid-solid surface tension, θ is the equilibrium contact angle. For refractories application the sessile drop test is used to follow the evolution of the contact angle as it can evolve with the temperature [12,[14][15][16][17] and composition [18][19][20][21][22][23][24].…”
Section: Hot Stage Microscopymentioning
confidence: 99%
“…The steel-refractory interaction was mainly affected by the chemical reaction and the steel penetration. [13][14][15] Thus, steel-refractory wettability had a strong influence on the steel penetration depth into the refractory. [16] Previous investigations mainly focused on the wettability between the steel and single-oxide materials, such as Al 2 O 3 and MgO.…”
Section: Introductionmentioning
confidence: 99%